2005
DOI: 10.1158/1078-0432.ccr-05-0275
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Matrilysin and Its Impact on Tumor Growth In vivo: The Potential Implications in Breast Cancer Therapy

Abstract: Introduction: Matrilysin (MMP-7) is a metalloproteinase that is involved in the degradation of extracellular matrix, invasion, and tumor progression. The current study examined if targeting matrilysin using retroviral ribozyme transgenes may have an impact on breast cancer cells and may have clinical implications. Experimental Design: Retroviral hammerhead ribozyme transgenes were designed to specifically target human matrilysin mRNA. The breast cancer cell MDA-MB-231was transfected with either a retroviral ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
1
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 27 publications
3
82
1
1
Order By: Relevance
“…Matrix metalloproteinase -7 (matrilysin 1) is a stromelysin, that degrades type IV collagen, fibronectin and laminin. It was shown that MMP-7 is aberrantly expressed in human breast tumours and that elimination of MMP-7 is associated with low invasiveness and slow tumour growth (Jian et al, 2005). Likewise, it has been recently reported that MMP-7 overexpression in breast cancer (MCF-7) cells enhances cellular invasiveness and activation of proMMP-2 and MMP-9 (Wang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinase -7 (matrilysin 1) is a stromelysin, that degrades type IV collagen, fibronectin and laminin. It was shown that MMP-7 is aberrantly expressed in human breast tumours and that elimination of MMP-7 is associated with low invasiveness and slow tumour growth (Jian et al, 2005). Likewise, it has been recently reported that MMP-7 overexpression in breast cancer (MCF-7) cells enhances cellular invasiveness and activation of proMMP-2 and MMP-9 (Wang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Other methods to inhibit or deactivate MT1-MMP have been reported. For example, Ro-28-2653, an inhibitor with high selectivity for MMP2, MMP9, and MT1-MMP has been shown to inhibit the in vitro invasion and reduce the growth of breast tumours of breast cancer cells (19 (25). It is indicated therefore that an approach targeting multiple MMPs may be necessary to have an impact when considering cancer therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid, extracted and purified using a plasmid extraction kit (Qiafilter, Qiagen, Crawley, UK), was introduced to a retroviral packaging cell line, PT67, using electroporation as previously described (25), followed by selection with G418 containing-medium for over 3 weeks. Viral titres from stably transfected PT67 cells were tested using NIH3T3 cells, and were found to be on average 8x10 5 cfu/ml.…”
Section: Construction Of Retroviral Hammerhead Ribozyme Transgenes Tamentioning
confidence: 99%
“…A standard procedure was used as previously described (18,19). Cells were plated into a 96-well plate (2,500 cells per well).…”
Section: In Vitro Cell Growth Assaymentioning
confidence: 99%